2010
DOI: 10.2353/ajpath.2010.090789
|View full text |Cite
|
Sign up to set email alerts
|

Adiponectin-Mediated Heme Oxygenase-1 Induction Protects Against Iron-Induced Liver Injury via a PPARα-Dependent Mechanism

Abstract: Protective effects of adiponectin (APN; an adipocytokine) were shown against various oxidative challenges; however, its therapeutic implications and the mechanisms underlying hepatic iron overload remain unclear. Herein, we show that the deleterious effects of iron dextran on liver function and iron deposition were significantly reversed by adiponectin gene therapy, which was accompanied by AMP-activated protein kinase (AMPK) phosphorylation and heme oxygenase (HO)-1 induction. Furthermore, AMPK-mediated perox… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
43
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 50 publications
(48 citation statements)
references
References 49 publications
(53 reference statements)
5
43
0
Order By: Relevance
“…Considering the importance of AMPK and C/EBP␤ in hepatocyte survival, it is predicted that AMPK-dependent C/EBP␤ activation may contribute to the ability of CDCA to maintain hepatocyte viability. This concept is in line with the previous findings that AMPK activation induces HO-1 via peroxisome proliferatoractivated receptor ␣ activation in the liver and protects cells from oxidative stress (Shin and Kim, 2009;Lin et al, 2010).…”
Section: Noh Et Alsupporting
confidence: 80%
“…Considering the importance of AMPK and C/EBP␤ in hepatocyte survival, it is predicted that AMPK-dependent C/EBP␤ activation may contribute to the ability of CDCA to maintain hepatocyte viability. This concept is in line with the previous findings that AMPK activation induces HO-1 via peroxisome proliferatoractivated receptor ␣ activation in the liver and protects cells from oxidative stress (Shin and Kim, 2009;Lin et al, 2010).…”
Section: Noh Et Alsupporting
confidence: 80%
“…NRF2 activators have been demonstrated to prevent iron-or diet-induced NASH (22,30). Additionally, heme oxygenase-1 has also been shown to play a protective role in concert with adiponectin against iron-induced injury in hepatocytes (15). Furthermore, the mRNA levels of XBP1, the UPR regulator, were downregulated in the DI mice.…”
Section: Discussionmentioning
confidence: 79%
“…For adenoassociated virus-ADIPOQ (AAV-ADIPOQ) and adenovirus-ADIPOQ (Adv-ADIPOQ) construction, full-length ADIPOQ cDNA was respectively cloned into the pAAV8-cytomegalovirus (CMV)-multiple cloning sites vector, and a human phosphoglycerate kinase (HPGK) promoter was used to drive ADIPOQ expression. The experimental protocol has been described in detail in prior studies (Lin et al, 2002(Lin et al, , 2010. The recombinant AAV-ADIPOQ (with 1 Â 10 12 viral particles in 50 ml of saline) was injected into a mouse tail vein (i.v.)…”
Section: Ironmentioning
confidence: 99%
“…Although iron chelation therapy is widely used to treat iron-overload conditions, recent data have shown that iron-overload cardiomyopathy is the primary determinant of cardiac complications and survival in these patients (Fraga and Oteiza, 2002). Lin et al (2010) demonstrated that adiponectin exerts its protective effects against iron-induced liver injury through peroxisome proliferator-activated receptor (PPAR)a-dependent heme oxygenase-1 (HO-1) induction. Cheng et al (2012) demonstrated a similar mechanism in which adiponectin exerts a protective effect against acute renal ischemia-reperfusion (I/R) injury through the prostacyclin-PPARa-HO-1 signaling pathway.…”
Section: Introductionmentioning
confidence: 99%